2013
DOI: 10.1097/01.pra.0000426324.67322.06
|View full text |Cite
|
Sign up to set email alerts
|

Delirious Mania

Abstract: Delirious mania is a severe but under-recognized neuropsychiatric syndrome characterized by the rapid onset of delirium, mania, and psychosis, not associated with a prior toxicity, physical illness, or mental disorder. Catatonia is often a prominent feature of the syndrome. While initially believed to be rare, recent reports suggest that delirious mania may constitute up to 15% of all acute mania cases. When delirious mania is unrecognized or improperly treated, it can progress rapidly in severity and can beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 68 publications
(105 reference statements)
1
26
1
1
Order By: Relevance
“…P. B. met some of the features of a patient with delirious mania as summarized by Jacobowski et al [3] and those described by other authors [8, 14, 16, 17]. A rapid onset of disorientation, fluctuating sensorium, altered level of consciousness, and severe cognitive dysfunction were noted.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…P. B. met some of the features of a patient with delirious mania as summarized by Jacobowski et al [3] and those described by other authors [8, 14, 16, 17]. A rapid onset of disorientation, fluctuating sensorium, altered level of consciousness, and severe cognitive dysfunction were noted.…”
Section: Discussionsupporting
confidence: 62%
“…The literature has recognized this concept in the form of clinical reports, but delirious mania has not been formally captured in a classification system such as the Diagnostic and Statistical Manual of Mental Disorders [2]. A reasonable definition of delirious mania is concurrence of rapid onset delirium, mania, and psychosis without association with a physical illness, prior toxicity, or another mental disorder [3]. Bell in 1849 identified that out of 1700 patients seen in McLean Asylum, USA, 40 patients presented with a “disease resembling some advanced stages of mania, and fever” [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECT is considered as a first line treatment in patients with delirious and severe mania, associated with life-threatening physical exhaustion [70, 71]. …”
Section: Introductionmentioning
confidence: 99%
“…The most severe forms equalled a syndrome with many names: Bells mania, delirium grave, delirium acutum, delirious mania, acute deadly psychosis and lethal/malignant catatonia [16, 43–45]. Thus, the Danish psychiatrist Erik Strömgren (1909-1993), in a chapter on reactive psychosis, wrote [46]: “If there is the slightest sign to the condition developing into the life-threatening delirum acutum (…), electroshock treatment is indicated.”…”
Section: Introductionmentioning
confidence: 99%